Factors affecting the motivation of community health workers: Perspectives from Accredited Social Health Activists (ASHA) in Uttar Pradesh, India - Dorinda ’t Hart; Jaya Menon; Dani J. Barrington; Arshe Alam; John Hembling; Deepti Pant; Rahul Dutta; Timothy Roberton (PLoS ONE, 2026)
Background Accredited Social Health Activists (ASHAs) are critical to extending health services to rural and underserved populations in India. Understanding what motivates these community health workers is essential for health organizations seeking to optimize their performance and retention. Objective To explore factors affecting the motivation of ASHAs in Uttar Pradesh, India, from the perspectives of the ASHAs themselves. Methods Qualitative in-depth interviews were conducted with 40 ASHAs across ten districts in Uttar Pradesh between September 6–24, 2023. ASHAs were selected based on the performance of their supervising ASHA Sanginis. Interviews were transcribed, translated from Hindi to English, and analyzed using thematic analysis in NVivo 12. Results Two categories of motivating factors emerged. Personal and community factors included self-efficacy from acquiring new knowledge, satisfaction from contributing to community health, increased autonomy and empowerment, and gaining respect within their communities. Organizational factors included training and skills development, supportive supervision from ASHA Sanginis, and financial incentives. While ASHAs remained positive about their work despite challenges, delayed payments and inadequate training were identified as key demotivating factors. Conclusions Health organizations can leverage organizational factors – adequate and timely training, supportive supervision, well-stocked drug kits, and timely remuneration – to support ASHAs’ intrinsic motivation. Failure to address these factors risks demotivation, reduced performance, and poorer health outcomes for the communities ASHAs serve.